Salivary Carriage of ESBL-Producing Coliforms in Root Canal Therapy Patients and Its Association with Antibiotic Use: A Brief Study - Rath, Shakti; Sahoo, Sanjit Kumar (Shahroud Journal of Medical Sciences, 2026)
Background: Saliva serves as a noninvasive medium for detecting extended-spectrum beta-lactamase (ESBL)-producing coliforms in patients undergoing root canal treatment (RCT). These bacteria have the potential to transfer antibiotic resistance genes to native oral biofilm microbes. Therefore, this study was done to check the presence of ESBL-producing coliform bacteria in the saliva of patients undergoing RCT and to explore their association with recent antibiotic use.Methods: The study was conducted in a Dental College and Hospital located in the capital city of an eastern Indian state. Two millilitres of unstimulated saliva were collected from 20 patients undergoing RCT. Saliva samples were routinely processed using standard microbiological methods to identify bacteria, and the double-disk synergy test was used to confirm ESBL strains.Results: Of the 20 saliva samples collected, 40% of the strains were identified as coliform bacteria. Furthermore, 3 of the 8 coliform isolates were identified as ESBL strains. ESBL colonisation showed a statistically significant association with prior antibiotic use (P-value=0.0079).Conclusion: This pilot study suggests that coliform and ESBL-producing bacteria may colonise the oral cavity of patients undergoing endodontic treatment; however, the findings should be interpreted cautiously due to the small sample size. These results highlight the importance of strict antibiotic stewardship in dental settings to limit the emergence and spread of resistant strains.